The poetic performance of philosophical discourse - de Alencar, Cesar (Revista Archai, 2024)
As from the perspective of a extensive research about what is specific to the philosophical discourse, we intend to demonstrate, in this paper, the necessary performative condition of philosophy in its origin. The concept of 'performance' is used here to establish an approximation between the poetics of the Greek aedos, studied in the first section, and the matrix of philosophical investigation on performative statements initiated by J. L. Austin, comprehended as decisive for the understanding of speech acts and the declarative statements in them communicated. From the focus of this approach, Plato's Dialogue takes on, through the dramatization of Socrates' original speech, the indication of the necessary philosophical concern with speech situations (appropriate to any true reflection on what utterances actually say) and simultaneously the condition that philosophical reflection itself happens due to the poetics of the act of telling the truth understood as a purgative effect of self-examination. In other words, philosophical discourse needs to be conceived, since the paradigm of Platonic Dialogue, as capable of carrying out the performance of self-examination as a work of reflection on acts and their contexts of speech, whose ethical, political and educational interest is the ultimate purpose of all analysis.